Exploring How Islamic Financial Literacy, Promotion, and Product Quality Affect Saving Intention Through Customer Trust as Mediator - Anita Rahmawaty; Dilla Ajeng Diah Saputri; Hidayatum Muafiyah; Widi Savitri Andriasari; Eni Kusrini (Indonesian Journal of Business Analytics, 2025)
This research aims to analyze the effect of Islamic financial literacy, promotion, and product quality on saving intention in Islamic microfinance with customer trust serving as mediator. The samples were selected from customers (n = 170) of Islamic microfinance institutions in Central Java, Indonesia. Data were collected using a questionnaire and the Partial Least Squares Structural Equation Modeling (PLS-SEM) as the data processing tool. The results of this research revealed that Islamic financial literacy and product quality have a positive and significant effect on customer trust and saving intention. However, the promotion failed to have a significant direct effect on customer trust. In addition, customer trust mediates the effect of Islamic financial literacy and product quality towards the saving intention of Islamic products in Islamic microfinance. Nevertheless, customer trust did not serve as a significant mediator for the effect of the promotion on saving intention. Therefore, Islamic microfinance practitioners are encouraged to enhance saving intention by focusing on Islamic financial literacy, promotion, product quality, and customer trust. Moreover, the promotion needs to be developed using appropriate strategies to increase customer trust.